Vegetable species used in areas degraded by mining (Research, Society and Development, 2019)
The mineral exploitation activities are of great importance and contribution to the Brazilian economy. The PRAD requirement and the relative care during the mine closure, according to the EIA / RIMA processes, are ensured in order to be returned with the quality and biodiversity, similar as what was previously found at the beginning of the project. Transposition of soil, seed bank, twings transposition, natural and artificial pollutants, nucleation and planting of plant seedlings. This research purses the species and didactic vegetables without use in the recovery of degraded areas in activities of exploitation of iron ore. A bibliographic review of scientific papers, doctoral theses and research on digital scientific sites and platforms was used using the key words: mining, revegetation, plant succession, mine closure and tree species in the last 10 years. The most frequent species of this species were: M. calodendron, L. pinaster and S. glabra, found in areas of initial environmental recovery, and Lychnophora pinaster, Symphyopappus brasiliensis, Baccharis serrulata, Chromolaena sp., Trichogonia sp. and Trixis vauthieri, intermediate rescue trees. For the recently published articles, the families Asteraceae, Podaceae and Orchidaceae are the ones that have the largest number of representatives in areas of recovery after mineral exploitation, due to the adaptability to exposed soil or low nutritional resources.The main resources of the same and the culture and the culture is in the field of grass-fat, pau-brasil and eucalipto culture keys in reestablishment of degraded areas. It is necessary the elaboration of a rich seed bank and an environmental species cataloging of the particles before the degradation activity, guaranteeing the success and the quick maintenance of the weed species.